METAPHORICAL CONCEPTUALIZATION OF HAPPINESS IN ISLAMIC BOARDING SCHOOL: A CASE STUDY IN INDONESIA - Devi Suci Windariyah; Imam Bonjol Juhari (Academic Bright Collaboration, 2026)
This study investigates the metaphors of happiness employed by santri in Indonesian Islamic Islamic boarding schools (Islamic boarding school) and examines how these metaphors reflect their emotional, social, and spiritual experiences. Utilizing a qualitative approach through participatory observation, in-depth interviews, and conceptual metaphor analysis, this research reveals that happiness is often metaphorized through spiritual imagery, such as “happiness is peace of mind” and “happiness is knowing God (ma‘rifatullāh).”These expressions illustrate how santri conceptualize happiness as intertwined with religious devotion, communal worship, and moral discipline. The santri's frame of mind, which varies from the expression of daily happiness, can also be influenced by the social and cultural context of the Islamic boarding school. In addition, the metaphor of happiness also plays an important role in shaping santri self-identity, strengthening collective ethics, internalizing religious values. This finding confirms that metaphor is not only a means of communication, but also a medium for conflicting meanings and social realities. The research contributes conceptually by applying metaphor theory within a traditional Islamic educational context and methodologically by highlighting local religious narratives in the study of language and emotion. These findings offer new directions for exploring the nexus of affect, spirituality, and discourse in Muslim minority and majority settings.